1997
DOI: 10.1007/s002469900120
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Interatrial Communications During the First Three Months of Life

Abstract: The objective of this study was to analyze retrospectively the results of color Doppler echocardiographic (CDE) investigations performed for the first time on a child under circumstances where there was unrestricted access to CDE. The records were obtained from a tertiary referral center at a university hospital serving a population of about one million. The patients were children (n = 284) ages 0 days to 15 years 9 months referred for CDE over a 1-year period. Heart abnormalities were found in 119 children (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 10 publications
1
14
0
2
Order By: Relevance
“…In different studies the incidence of IASOs was reported to be between 63.6% and 78.0%, 67.8%, 92.0% in children who were less than 1 year of age [5,11], at 2-7 days of age [6] and at 1 h of age [12] respectively. Our results (78.1% for term neonates and 83.3% for preterm neonates, overall 78.6%) were comparable with the other studies.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In different studies the incidence of IASOs was reported to be between 63.6% and 78.0%, 67.8%, 92.0% in children who were less than 1 year of age [5,11], at 2-7 days of age [6] and at 1 h of age [12] respectively. Our results (78.1% for term neonates and 83.3% for preterm neonates, overall 78.6%) were comparable with the other studies.…”
Section: Discussionmentioning
confidence: 96%
“…Since there are no definitive diagnostic criteria for both patent foramen ovale (PFO) and secundum atrial septal defects (ASD), it is difficult to differentiate these two lesions, particularly in the newborn period. We, as some authors [5,6], called these two lesions as ''interatrial septal openings (IASOs)''. The objectives of this study were to establish the prevalence of IASOs diagnosed in the first days of life, to define the natural course of them during the first year of life, and to find the factors affecting the spontaneous closure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of 102 healthy newborns showed that 62% had an ASD during the first days of life and at follow-up after median 2.3 months, 48 of 89 (55%) still had a left-to-right atrial shunt through an ASD of more than 3 mm [12]. In 113 first time echocardiographies in infants of less than three months, 61 were found to have an inter-atrial communication (secundum ASD) [13]. In this study 31% of the infants with ASD were born preterm and the rate of spontaneous closure was higher although not significant than in infants born at term.…”
Section: Asdmentioning
confidence: 96%
“…Since there are no definitive diagnostic criteria for both patent foramen ovale and secundum atrial septal defects, it is difficult to differentiate these two lesions by echocardiography, particularly in the early newborn period. Some authors, called these two lesions as "interatrial septal openings (IASOs)" [20][21][22]. We greatly appreciated the letter to the Editor by Rana Olgunturk and Serdar Kula [1] but the diagnosis was made not only on the basis of the first observation but also on the basis of the persistence of abnormalities during the longterm follow-up and therefore the infant was referred to a pediatric heart surgical unit where the abnormalities were confirmed.…”
mentioning
confidence: 96%